Antibodies to the atherosclerotic plaque components beta2-glycoprotein I and heat-shock proteins as risk factors for acute cerebral ischemia - Henrique Luiz Staub; Gary Lewis Norman; Tiffany Crowther; Viviane Roseli da Cunha; Aline Polanczyk; Jussara Maria Bohn; Jefferson Gomes Fernandes; Wiliam Habib Chahade; Carlos Alberto von Mühlen (Arquivos de Neuro-Psiquiatria)
One third of cases of cerebral ischemia have no clear etiology. A humoral response to the atherosclerotic plaques components beta2-glycoprotein l (beta2-gpl) and heat-shock proteins (Hsp) might be involved in the pathogenesis of stroke. This case-control study includes a complete profile of anti-beta2-gpl antibodies and testing of IgG antibodies to the 60/65 kilodaltons (kDa) Hsp in stroke patients. Ninety-three patients with acute ischemic stroke and 93 controls were evaluated for age, sex, race, hypertension, smoking, previous cardiopathy, diabetes mellitus, hypercholesterolemia and previous history of cerebral ischemia. lgG/lgM/lgA anticardiolipin (aCL) and anti-beta2-gpl antibodies, as well as lgG antibodies to human 60 kDa Hsp and to Mycobacterium bovis 65 kDa Hsp, were detected by immunoassay. Adjusted odds ratios (OR) were calculated by logistic regression. The adjusted OR for IgA anti-beta2-gpl antibodies was 4.6 (90%Cl 1.5 to 14.3; p = 0.025). The non-adjusted OR for IgG antibodies to Hsp 60 was 26.1. The adjusted OR for IgG antibodies to Hsp 65 was 3.2 (90%Cl 1.2 to 8.3; p = 0.044). The adjusted OR for lgG to any Hsp (60 or 65) was 4.8 (90%Cl 1.9 to 12.1; p = 0.006). This study demonstrates that elevated IgA anti-beta2-gpl and lgG anti-Hsp 60/65 antibodies are associated with increased risk of ischemic stroke. The association occurred independently of other risk factors. This humoral response might link autoimmunity, thrombophilia and atherosclerosis in stroke patients.